Prognoza i ocena trafności stóp zwrotu portfela papierów wartościowych z wykorzystaniem standardowej miary ryzyka oraz miary ryzyka RiskGrade - Arczewski, Robert; Osękowski, Marek (The Forecast and Evaluation of the Accuracy of the Return Rates of Portfolio Securities on the Basis of the Standard Risk Measurement and the RiskGrade Measurement, 2006)
The purpose of the article is to compare the accuracy of the expected return rates of portfolio securities formed on the basis of the standard (classical) risk measurement and the RiskGrade methodology. The article presents a method of forming these portfolios for chosen associations, quoted at the Stock Exchange between 2nd January 2001 and 31st August 2005, on the basis of given formulas and assumptions. The authors interpret the achieved results as regards the percent of particular shares in a given portfolio and investigate the differences between the expected value of the return rates of portfolios and their real value.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1112, s. 39-48